Composite wastewater treatment by aerated electrocoagulation and modified peroxi-coagulation processes. (August 2018) - Kumar, Abhijeet; Nidheesh, P.V.; Suresh Kumar, M.
Abstract: Treatment of composite wastewater generating from the industrial estates is a great challenge. The present study examines the applicability of aerated electrocoagulation and modified peroxi-coagulation processes for removing color and COD from composite wastewater. Iron plates were used as anodes and cathodes in both electrochemical processes and experiments were carried out in a working volume of 2 L. Aeration enhanced the efficiency of electrocoagulation process significantly. More than 50% of COD and 60% of color were removed after 1 h of electrocoagulation process operated at pH 3 and applied voltage of 1 V. Efficiency of the modified peroxi-coagulation process was significantly higher than that of aerated electrocoagulation. COD and color removal efficiencies of the modified peroxi-coagulation process were found as 77.7% and 97%, respectively after 1 h of electrolysis operated at 1 V, solution pH 3 and 50 mM hydrogen peroxide addition. This improved efficiency of modified peroxi-coagulation compared to aerated electrocoagulation is mainly due to the attack of in-situ generated hydroxyl radicals. Highlights: Electrochemical treatment of composite wastewater. Enhanced performance of electrocoagulation with external aeration. Superior performance of modified peroxi-coagulation process than aerated electrocoagulation process. Active chlorine generation is irrespective of process and pH. Hydroxyl radicals are superior oxidant responsible for pollutant removal.